The Interplay between ROS and Ras GTPases: Physiological and Pathological Implications. (30th November 2011) - Ferro, Elisa; Goitre, Luca; Retta, Saverio Francesco; Trabalzini, Lorenza
Abstract : The members of the RasGTPase superfamily are involved in various signaling networks responsible for fundamental cellular processes. Their activity is determined by their guanine nucleotide-bound state. Recent evidence indicates that some of these proteins may be regulated by redox agents. Reactive oxygen species (ROSs) and reactive nitrogen species (RNSs) have been historically considered pathological agents which can react with and damage many biological macromolecules including DNA, proteins, and lipids. However, a growing number of reports have suggested that the intracellular production of ROS is tightly regulated and that these redox agents serve as signaling molecules being involved in a variety of cell signaling pathways. Numerous observations have suggested that some Ras GTPases appear to regulate ROS production and that oxidants function as effector molecules for the small GTPases, thus contributing to their overall biological function. Thus, redox agents may act both as upstream regulators and as downstream effectors of Ras GTPases. Here we discuss current understanding concerning mechanisms and physiopathological implications of the interplay between GTPases and redox agents.